MODELING AND ANALYSIS OF A STANDALONE PV–HYDROGEN MICROGRID FOR DECENTRALIZED ENERGY SUPPLY - BARLA E.M. (Journal of Sustainable Energy)
This study investigates the modeling and performance analysis of a standalone photovoltaic (PV) – hydrogen microgrid designed to support decentralized energy supply in off-grid applications. The system architecture includes a PV array powering an electrolyzer for green hydrogen production, a hydrogen storage tank, and a proton exchange membrane (PEM) fuel cell used for energy recovery during periods of low solar availability. A constant electric load is considered, with all components integrated through a shared DC bus to enhance system efficiency and reduce conversion losses. The study confirms the potential of PV - hydrogen hybrid systems as a sustainable solution for clean, decentralized power in remote and off-grid environments.